Keberkesanan kaedah pengajaran berasaskan teknologi mudah alih di kalangan guru pendidikan Islam dalam meningkatkan mutu pengajaran dan pembelajaran - Sylviano, Abu Bakar (2020)
Most of the past research shows that teachers are fewer in applying mobile teaching technology in schools compared to the traditional ones. Anyhow, there is no research yet on Islamic Education teachers’ readiness toward mobile technology teaching approach in terms of knowledge, usage, and attitude. Therefore, the follow-up steps are hardly to be taken by the administrators and the teachers themselves. Any existing mobile teaching technology models are too tricky to be adapted and adopted by Islamic Education teachers in schools. Hence a research on Islamic Education teachers’ readiness on knowledge, usage, and attitude towards mobile teaching technology approach should be done before the mobile teaching technology approach would be applied effectively. Some mobile teaching models are being adapted by teachers without considering their effectiveness and suitability. They just plug and play the mobile technics even they have no idea either the technics is comply and facilitated or not. Are those mobile teaching approach really comply for them? Are those mobile teaching approach really facilitating them to teach? These two questions require a new research to be done in how good and bad some existing models, or any improvements needed? The research involved 130 samples from Islamic Education teachers in Mersing, Johore. Data was collected using a set of questionnaires and had been analysed quantitatively. Quantitative analysis also had been done during some interview session amongst ten Coordinators in Chief for Islamic Education subject. Through the qualitative and quantitative analysis, the researcher reform and proposes a new conceptual model on mobile teaching approach which integrates technology and practise. The findings show that the Islamic Education teachers in Mersing, Johore strongly ready to adapt and apply the new conceptual mobile teaching approach while a 60 primary schools students involved in the research agreed that the teaching and learning process become easier and more understandable.